Combinatorics of Speech Etiquette Formulas in Communicative Situation “Response to Gratitude” in English Language - M. V. Vlavatskaya (Tsentr nauchnykh i obrazovatelnykh proektov, 2017)
The article describes the combinatorial potential of the formulas of speech etiquette in the context of the situation “response to gratitude” in the English picture of the world. The research is conducted in the framework of combinatorial linguistics that studies the linear relations of language units and their combinatorial potential, and more precisely in the framework of combinatorial syntax, studying the combinatorics of units of language and speech (words, phrases, sentences, statements) in a specific situation of communication. Material of the research were the dialogues from the films and life of native English speakers, collected using the method of linguistic observation. The urgency is determined by the relevance in the current study of functionally-speech aspect of language in general and syntactic transformations of the units of etiquette with identical function and semantics in particular. Special attention in article is paid to the combinatorial nature of the formulas of speech etiquette in English language. The author’s purpose of the study is to determine the set of formulas used in the situation of communication “response to gratitude.” For its implementation specific problems are put and solved that include identifying features of the formulas of speech etiquette, as well as determining the number, shapes and additional functions of formulas in this situation of communication. In conclusion, the results of studies are given concerning the language specifics of units of speech etiquette and their national culture specifics.